Suplementos alimentares: adequabilidade à legislação e efeitos metabólicos em ratos - Ferreira, Alan de Carvalho Dias (2010)
Dietary supplements are widely consumed by exercise practitioners and athletes. Researchers have noted the inadequacy of such products, as well as the presence of androgens, increasing suspicion about their true composition. The objective of this research was to list and classify food supplements sold in retail outlets in Joao Pessoa, check the products suitability to existing laws; to analyze the effects in young rats subjected to exercise, caused by the chronic ingestion of supplements widely marketed on: food intake and body weight gain, levels of total testosterone, and body composition (fat percentage and lean mass). In a survey of descriptive and experimental field, at first, we identified the products sold in Joao Pessoa city, represented by pharmacies, specialized stores and supermarkets. We compared the composition and characteristics of supplements labeled with the minimal of composition and quality set by Ordinance 222/98 ANVISA. Products that were not included in the Ordinance were classified among categories according to their composition and/or its market name. In the experimental work, sixty young male Wistar rats were distributed into five groups (n = 12/group) (TC - trained control; SC sedentary control; ST1 supplemented/trained 1; ST2 - supplemented/trained 2; ST3 - supplemented/trained 3). By gavage, ST1, ST2 and ST3 received 2.5g of each supplement and TC and SC got filtered water. Animals weight and food intake were measured weekly. After eight weeks, animals were sacrificed and blood concentration of total testosterone were measured and carcasses fat and protein determination. A total of 945 different products were determined, most of them (43%) considered Foods for Physical Activity Practitioners (FPAP) and 28% of products forbidden in Brazilian market. Among the FPAP, none of them had all the legislation features, mainly because it contains, according to the products labeling, vitamins and minerals excess, or may not show the minimum amount of protein. Considering the studied supplements, 42% showed inadequate designation and 33% showed forbidden expressions. The results of experimental work showed that both exercise and supplementation promoted less weight gain (p<0.05). The exercise did not alter the levels of total testosterone, however, the three supplements promoted reduction of testosterone levels (p <0.001). Fat percentage of ST1, ST2 and ST3 groups showed two times higher than the TC group (p<0.001). TC showed the amount of total body protein higher (p<0.05) than the supplemented groups. The high inadequacy rate, mainly with vitamins and minerals excess and the lower proportion of labeled proteins, demonstrates the need for supplements control according to the law. The suitability assessment allows to see if the supplement or group of supplements containing the nutrients minimum levels to generate their expected impact, either in performance, health or nutrition. The data indicate that chronically supplements caused an increase of adipose tissue, lower gain muscle mass and lower weight gain, mainly because of the decreased secretion of testosterone. Similar results for the three supplements tested support the hypothesis that they contain androgens or their precursors.